Histopathological study of prostatic lesions in correlation with serum prostate specific antigen levels in elderly men - Deshpande, Nikhil S.; Dahe, Swati V.; Munemane, Anil B.; Dhokikar, Gajanan D.; Karle, Ravindra R. (International Journal of Research in Medical Sciences, 2020)
Background: Prostatic lesions are common among elderly men with urinary complaints. Variety of prostatic lesions range from inflammatory, benign to malignant pathologies. The Prostate specific antigen (PSA) is secreted by glandular epithelium of prostate shows raised serum levels in these pathologies. Usually significant rise is commonly associated with Prostatic adenocarcinomas (PCa) with exceptions. Methods: In this retrospective study, total 63 diagnosed cases of prostatic lesions over a one-year period for which serum PSA levels were available, were selected. Cases without serum PSA levels & inadequate biopsies were excluded. Histological diagnosis of prostatic lesions reconfirmed and its correlation with serum PSA was done. Results: Study included patients with mean age 67.84 years (range: 48-60) at the time of diagnosis. Benign lesions were commonest prostatic lesions accounting for total 54 cases (85.71%) out of which 38 were of Benign prostatic hyperplasia (BPH), 14 cases of BPH with prostatitis while single case each for BPH with granulomatous prostatitis and basal cell hyperplasia. Mean PSA value for benign lesions was 6.57 ng/ml. Total 8 were malignant which included 7 (11.11%) PCa while single (1.59%) case of metastatic transitional cell carcinoma. Mean PSA for PCa were 35.05 ng/ml. Single case (1.59%) of high grade prostatic intraepithelial neoplasia also detected. Conclusion: Common age group at the time of presentation of prostatic pathologies is 60-70 years. The most common prostatic lesions are benign predominantly BPH. PCa are commonest malignancies. Elevated PSA levels >20 ng/ml are commonly observed in PCa. However lower or normal values don’t rule out PCa.